2007
DOI: 10.1007/bf03346327
|View full text |Cite
|
Sign up to set email alerts
|

Serum testosterone level and related metabolic factors in men over 70 years old

Abstract: Total testosterone level is significantly related to metabolic and inflammatory factors in elderly men. Low total testosterone may be a significant indicator for development of metabolic syndrome in elderly men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…In our sample, FAI and total testosterone did not correlate with BMI, either in the whole sample or after splitting by group. We found a correlation between waist to hip ratio only in control subjects and total testosterone (not FAI) which is reported in the literature (20). Psychotic subjects did not show this correlation, supporting the view that they present a different metabolic pattern.…”
Section: Discussionsupporting
confidence: 83%
“…In our sample, FAI and total testosterone did not correlate with BMI, either in the whole sample or after splitting by group. We found a correlation between waist to hip ratio only in control subjects and total testosterone (not FAI) which is reported in the literature (20). Psychotic subjects did not show this correlation, supporting the view that they present a different metabolic pattern.…”
Section: Discussionsupporting
confidence: 83%
“…Most prior cross-sectional studies have observed inverse associations between androgen concentrations and inflammatory biomarkers (Laaksonen et al 2003; Bhatia et al 2006; Tang et al 2007; Schneider et al 2009; Kaplan et al 2010; Kupelian et al 2010; Brand et al 2012; Zhang et al 2012). A recent study in Chinese men showed that lower concentrations of total and calculated free testosterone were associated with higher CRP concentration (Zhang et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Two randomized controlled trials of androgen replacement therapy in hypogonadal men reported a decrease in the concentration of pro-inflammatory cytokines in the active therapy arm (Malkin et al 2004; Kalinchenko et al 2010), but other trials did not confirm these findings (Ng et al 2002; Singh et al 2002; Kapoor et al 2007; Nakhai-Pour et al 2007). A few epidemiologic studies have evaluated the cross-sectional association between sex steroid hormones and inflammatory biomarkers in men, but had inconsistent results (Laaksonen et al 2003; Van Pottelbergh et al 2003; Bhatia et al 2006; Maggio et al 2006; Nakhai Pour et al 2007; Tang et al 2007; Maggio et al 2009; Schneider et al 2009; Kaplan et al 2010; Kupelian et al 2010; Brand et al 2012; Zhang et al 2012). Moreover, some of the latter studies did not adjust for important confounders (e.g., smoking and obesity) (Laaksonen et al 2003; Van Pottelbergh et al 2003; Bhatia et al 2006; Tang et al 2007; Kaplan et al 2010), and very few studies mutually adjusted for other sex hormones (Nakhai Pour et al 2007; Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available evidence from these RCTs generally shows little effect of testosterone therapy on CRP (Aversa et al, 2010;Frederiksen et al, 2013;Kapoor et al, 2007;Nakhai-Pour et al, 2007;Ng et al, 2002), white blood cell count (Kalinchenko et al, 2010) or fibrinogen (Smith et al, 2005), although one RCT reported testosterone decreased CRP (Kalinchenko et al, 2010) among a subset of men. Larger observational studies among men usually, but not always, report serum testosterone inversely associated with CRP (Gannage-Yared et al, 2011;Haring et al, 2012;Kupelian et al, 2010;Laaksonen et al, 2003;Nakhai Pour et al, 2007;Zhang et al, 2013), white blood cell counts and/or its differentials (Brand et al, 2012;Haring et al, 2012;Tang et al, 2007) and fibrinogen (Bonithon-Kopp et al, 1988;Haring et al, 2012;Yang et al, 1993). Experimental and observational evidence may differ for a number of reasons: the small size of most RCTs of testosterone therapy, differences in the action of exogenous and endogenous testosterone, serum testosterone acting as a marker of health status or serum testosterone not capturing all androgen activity (Labrie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%